Application of the tensegrity system to create 3D impression of the butterfly body heliconius doris obscurus as a floating compression structure. Issue 1 (2nd January 2018) - Rochman, Dina; Sánchez, América
ABSTRACT: In this paper we present the research carried out at the Metropolitan Autonomous University Campus Cuajimalpa, which consists of developing a floating structure of the body of the Heliconius Doris obscurus, worldwide known as Laparus Doris obscurus (Weymer, 1891), based on Karl Ioganson invention "Tensegrity". In this project, we made three prototypes in order to study the way the structure of floating compression of the butterfly body is performed. The first prototype is a solid structure printed in 3D. This prototype was used to analyze the curvature of the butterfly body. In the second and third prototype, the butterfly body was divided in 24 parts. In the second prototype, we use a three-dimensional network of nylon monofilament and plastic straws as separators between each part to tense and join each of the parts. In each part, in the third prototype two holes were open to place two cylinders with four holes; between each part one cylinder with eight holes added, in order to pass the nylon monofilament to stress the body. The objective of this project is that design students use the techniques of geometric morphometrics, descriptive geometry and tensegrity for their terminal projects. GRAPHICAL ABSTRACT: